The "Coase Theorem": A Reexamination–Comment - Jaffe, Jeffrey F. (Quarterly Journal of Economics, 1975)
Journal Article The “Coase Theorem”: A Reexamination—Comment Get access Jeffrey F. Jaffe Jeffrey F. Jaffe University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 89, Issue 4, November 1975, Pages 660–661, https://doi.org/10.2307/1884701 Published: 01 November 1975